The Prevalence of Nosocomial Infections in Iranian Hospitals - M Mohammadi; AA Vaisi Raiegan; R Jalali; A Ghobadi; N Salari; H Barati (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2019)
BACKGROUND AND OBJECTIVE: Nosocomial infections are one of the major health problems. As the length of stay in the hospital increases, the risk of mortality and morbidity increases, which ultimately increases the cost of treatment. Therefore, the present study was performed as a systematic review and meta-analysis to evaluate the prevalence of nosocomial infections in Iran. METHODS: This systematic review and meta-analysis was performed in the range of the years 2001 – 2017. Articles related to the topic were assessed using Persian keywords “nosocomial infections”, “hospital”, and “Iran”, and their English equivalent in descriptive and cross sectional studies by searching online databases of SID & Magiran, PubMed and Scopus, ScienceDirect and Google Scholar. Analytical and interventional studies were excluded from the study list. FINDINGS: 578 articles had the preliminary inclusion criteria, and with the removal of 568 unrelated or low quality articles during secondary analyses, 10 articles were finally included in the process of meta-analysis. The overall prevalence of nosocomial infections in Iranian hospitals was 4.6% (CI-95%: 2.6 – 8.1). The highest prevalence of nosocomial infections was in Sanandaj with 15.6% (CI-95%: 10.22–82.1) and the lowest prevalence was in Urmia with 0.4% (CI-95%: 0.1–1.01). CONCLUSION: The results of the study showed that nosocomial infection has a low prevalence in Iran, but more attention and control over nosocomial infections in Iranian hospitals is necessary to reach standard levels.